Double shear strength of B.S.L.69 snap head rivets in L.72 and L.73 aluminium alloy sheet - Howe, D. (College of Aeronautics, 1956)
A limited series of tests has been carried out on single and double shear riveted joints using 1469 (D.T.D.327) snap head rivets and L.72 (D.T.D.610) and L.73 (D.T.D. 546) sheets. The specimens were similar to those used by the Royal Aeronautical Establishment (ref.1), the double shear specimens being essentially two single shear specimens placed back to back. In each case the 1 per cent, 2 per cent and ultimate strengths were found, the single shear values being in agreement with the equivalent R.A.E. tests (ref. 2). It was found that at high bearing stresses the permissible shear stress in the double shear joint falls below that of the single shear joint having the same nominal bearing stress, This reduction of permissible shear stress was found to increase with joint extension and to be independent of the sheet materials tested. Design curves are given.